Who Does the Talking Here? The Impact of Gender Composition on Team Interactions - David Hardt; Lea Mayer; Johannes Rincke (Center for Economic Studies and ifo Institute (CESifo), 2023)
We analyze how the gender composition of teams affects team interactions. In an online experiment, we randomly assign individuals to gender-homogenous or gender-mixed teams. Teams meet in an audio chat room and jointly work on a gender-neutral team task. By design, effects on team performance can only work through communication. We find that all-male teams communicate more than all-female teams and outperform teams of both alternative gender compositions. In mixed teams, males strongly dominate the team conversation quantitatively. Past exposure to gender-mixed teamwork makes females more reluctant to engage in mixed teams, while for males the opposite is true.
Keywords: C92; C93; D83; J16; 330; teams; teamwork; gender composition; communication; team performance; preference for teamwork; online experiment